A comparison of different experimental methods for general recombination correction for liquid ionization chambers - Andersson, Jonas; Jäkel, Oliver (Physics in medicine and biology, 2012)
Radiation dosimetry of highly modulated dose distributions requires a detector with a high spatial resolution. Liquid filled ionization chambers (LICs) have the potential to become a valuable tool for the characterization of such radiation fields. However, the effect of an increased recombination of the charge carriers, as compared to using air as the sensitive medium has to be corrected for. Due to the presence of initial recombination in LICs, the correction for general recombination losses is more complicated than for air-filled ionization chambers. In the present work, recently published experimental methods for general recombination correction for LICs are compared and investigated for both pulsed and continuous beams. The experimental methods are all based on one of two approaches: either measurements at two different dose rates (two-dose-rate methods), or measurements at three different LIC polarizing voltages (three-voltage methods). In a comparison with the two-dose-rate methods, the three-voltage methods fail to achieve accurate corrections in several instances, predominantly at low polarizing voltages and dose rates. However, for continuous beams in the range of polarizing voltages recommended by the manufacturer of the LICs used, the agreement between the different methods is generally within the experimental uncertainties. For pulsed beams, the agreement between the methods is poor. The inaccuracies found in the results from the three-voltage methods are associated with numerical difficulties in solving the resulting equation systems, which also make these methods sensitive to small variations in the experimental data. These issues are more pronounced for the case of pulsed beams. Furthermore, the results suggest that the theoretical modelling of initial recombination used in the three-voltage methods may be a contributing factor to the deviating results observed.